Exploiting biospectroscopy as a novel screening tool for cervical cancer: towards a framework to validate its accuracy in a routine clinical setting. (November 2013) - Purandare, Nikhil C; Trevisan, Júlio; Patel, Imran I; Gajjar, Ketan; Mitchell, Alana L; Theophilou, Georgios; Valasoulis, George; Martin, Mary; von Bünau, Günther; Kyrgiou, Maria; Paraskevaidis, Evangelos; L Martin-Hirsch, Pierre; et al.
Biospectroscopy is an emerging field that harnesses the platform of physical sciences with computational analysis in order to shed novel insights on biological questions. An area where this approach seems to have potential is in screening or diagnostic clinical settings, where there is an urgent need for new approaches to objectively interrogate large numbers of samples in an objective fashion with acceptable levels of sensitivity and specificity. This review outlines the benefits of biospectroscopy in screening for precancer lesions of the cervix due to its ability to separate different grades of dysplasia. It evaluates the feasibility of introducing this technique into cervical screening programs on the basis of its ability to identify biomarkers of progression within derived spectra ('biochemical‑cell fingerprints').